Degree of TCR internalization and Ca2+ flux correlates with thymocyte selection. - Mariathasan, S; Bachmann, M; Bouchard, D; Ohteki, T; Ohashi, P (1998)
Recent evidence suggests that TCR down-regulation directly reflects the number of TCRs that have engaged MHC/peptide ligand complexes. Here, we examined the influence of defined peptides on thymic selection based on their ability to induce differential TCR internalization. Our results demonstrate that there is a direct correlation: peptides that induce strong TCR down-regulation are most efficient at mediating negative selection, whereas peptides that induce suboptimal TCR internalization are more efficient at triggering positive selection. As a consequence of suboptimal TCR internalization, a proportion of TCR complexes that remain on the cell surface may be able to relay continual signals required for survival and differentiation. In addition, we show that the magnitude of Ca2+ influx set by these peptides reflects the hierarchy of TCR down-regulation and correlates with positive vs negative selection of transgenic thymocytes. Together, our data suggest that T cell selection is mediated by differing intensities of the same TCR-mediated signal, rather than by distinct signals.